2014
DOI: 10.3390/ijms150610974
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise Promotes Recovery of Neurological Function after Ischemic Stroke in Rats

Abstract: Although physical exercise is an effective strategy for treatment of ischemic stroke, the underlying protective mechanisms are still not well understood. It has been recently demonstrated that neural progenitor cells play a vital role in the recovery of neurological function (NF) through differentiation into mature neurons. In the current study, we observed that physical exercise significantly reduced the infarct size and improved damaged neural functional recovery after an ischemic stroke. Furthermore, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…The rats of both CFA exercise group and sham exercise group were trained on two specially designed roller treadmills for 7 days/week, and each treadmill allowed three rats to run simultaneously. Adjustments in the motor speed and exercise duration were implemented via a control panel connected to a genemotor [ 24 , 25 , 26 ]. To allow for a transition, the daily running duration lasted 20 min/day (9 m/min) for the first week, was increased to 30 min/day (11 m/min) for the second week, and was then increased to 40 min/day (13 m/min) from the third to eighth weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The rats of both CFA exercise group and sham exercise group were trained on two specially designed roller treadmills for 7 days/week, and each treadmill allowed three rats to run simultaneously. Adjustments in the motor speed and exercise duration were implemented via a control panel connected to a genemotor [ 24 , 25 , 26 ]. To allow for a transition, the daily running duration lasted 20 min/day (9 m/min) for the first week, was increased to 30 min/day (11 m/min) for the second week, and was then increased to 40 min/day (13 m/min) from the third to eighth weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown that animals exposed to locomotor exercise beginning 24–48 h post-stroke have better behavioral outcomes and smaller ischemic volumes than control animals who receive delayed or no exercise training [3135]. One study directly compared initiation of treadmill training at different time points and found behavioral gains in rats who began training at 5 days, and to a lesser extent 14 days, but not 30 days post-stroke.…”
Section: Neuroplastic Changes Following Strokementioning
confidence: 99%
“…Ischemic stroke is a major cause of mortality and disability worldwide (192). Aerobic exercise reduces the risk for ischemic stroke and can improve functional and morphological recovery after stroke (21,193).…”
Section: Cortical Strokementioning
confidence: 99%